1985
DOI: 10.1038/clpt.1985.166
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent absorption of amoxycillin and bacampicillin

Abstract: The relationship between the relative absorption and increasing oral doses of amoxycillin and bacampicillin, a prodrug of ampicillin, was studied testing the hypothesis that a saturable transport system for aminopenicillins exists in the human gut. Each drug was given in four different doses in a randomized order to 12 fasting subjects. One group of subjects was given amoxycillin in single doses of 375, 750, 1500, and 3000 mg, while the other group received bacampicillin in 400, 800, 1600, and 3200 mg doses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 1 publication
7
45
0
Order By: Relevance
“…Although there was a correlation between renal function and plasma clearance or renal clearance for ampicillin and amoxycillin, the plasma and renal clearances were essentially similar after amoxycillin and after ampicillin in this study compared to those previously reported in younger volunteers (Sjovall et al, 1985b) (Table 6). The mean fraction of the drug excreted unSlightly higher distribution volumes and changed in the urine was the same in these old plasma half-lives were seen in the elderly for subjects as in younger ones indicating a similar both drugs.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Although there was a correlation between renal function and plasma clearance or renal clearance for ampicillin and amoxycillin, the plasma and renal clearances were essentially similar after amoxycillin and after ampicillin in this study compared to those previously reported in younger volunteers (Sjovall et al, 1985b) (Table 6). The mean fraction of the drug excreted unSlightly higher distribution volumes and changed in the urine was the same in these old plasma half-lives were seen in the elderly for subjects as in younger ones indicating a similar both drugs.…”
Section: Discussionsupporting
confidence: 57%
“…as these drugs are considered to be distributed (Sjovall et al, 1985b mainly to the extracellular fluid. A decrease in the volume of distribution with age is then expected, due to a decrease in the total body water with increasing age (Crooks et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this research has been carried out in rats on the basis of the assumption that rats represent suitable experimental animals for the elucidation of the absorption mechanisms of amino-plactam antibiotics in humans. From the results of those investigations, it has been suggested that saturable carrier-mediated transport is involved in the intestinal absorption of these antibiotics in rats (7,15), and the absorption features of amoxicillin in humans have sometimes been interpreted on the basis of such a mechanism (10,18). However, few investigators have assessed the suitability of using the rat as the animal model for studies of the bioavailability of amoxicillin (14) and other amino-1-lactam antibiotics after oral administration (2).…”
mentioning
confidence: 99%
“…The reasons for the difference between results obtained by Ingold (11) and those of the other studies, including those described here, are not clear since the procedures used in all these investigations were similar, with the exception of the study by Lovering and colleagues (17), in which the peak levels were observed following intravenous administration of the dose. The sputum pharmacokinetic data suggest that the delay in amoxicillin penetration into the lung secretions is about 0.5 to 2.5 h, since previous studies report that the peak level in serum in healthy fasting subjects is achieved 1.5 h after patients receive the drug (25,33). The predose sputum collection was made 8 h after the previous dose of amoxicillin.…”
Section: Methodsmentioning
confidence: 99%